Economic Growth, Corporate Earnings And Equity Returns: Evidence From Central And Eastern European Countries - Gajdka, Jerzy; Pietraszewski, Piotr (Comparative Economic Research. Central and Eastern Europe, 2016)
This paper discusses the links between economic growth, corporate earnings and stock returns. Cross-country correlation studies do not confirm the intuitive assumption that higher returns on equities are more likely in the fastergrowing countries. The problem can be analysed more deeply by analysing stock returns with respect to the growth of earnings per share (EPS) and changes in valuation (P/E ratio). Within this framework, two types of factors explaining the lack of correlation between GDP growth and stock returns are distinguished. The empirical research on developed and emerging market countries reveals that in the long run stock price returns are driven by companies’ earnings, and that the lack of correlation between GDP growth and equity returns is almost fully explained by the divergence between GDP growth and EPS growth. In this article the results of an investigation into this area, based on a sample of post-communist Central and Eastern European countries, are presented and discussed. It was found that in these countries changes in valuation (P/E ratio) appear to play an important role, cancelling the impact of EPS growth on stock returns.